Sebuah Usaha Mencari Kasih Sayang: Kajian Semiotika dan Struktur Narasi Cerpen “Ketika Gerimis Jatuh” Karya Sapardi Djoko Damono - Khothibul Umam (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
This study aims to examine the short story "Ketika Gerimis Jatuh" by Sapardi Djoko Damono. The method used in this research is by the approach of narrative structure and semiotics. Semiotic study with a focus on syntagmatic and paradigmatic analysis can describe the relationship of Rini, gerimis (drizzle), and his family. With a focus on syntagmatic and paradigmatic analysis can be found criticism of the modern lifestyle of parenting in children.